2015
DOI: 10.1371/journal.pone.0136304
|View full text |Cite
|
Sign up to set email alerts
|

The Prostaglandin E2 Receptor EP4 Regulates Obesity-Related Inflammation and Insulin Sensitivity

Abstract: With increasing body weight, macrophages accumulate in adipose tissue. There, activated macrophages secrete numerous proinflammatory cytokines and chemokines, giving rise to chronic inflammation and insulin resistance. Prostaglandin E2 suppresses macrophage activation via EP4; however, the role of EP4 signaling in insulin resistance and type 2 diabetes mellitus remains unknown. In this study, we treated db/db mice with an EP4-selective agonist, ONO-AE1-329, for 4 weeks to explore the role of EP4 signaling in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…This was further supported by the enhanced coronary vasodilator effect found for the selective EP 4 receptor agonist TCS 2519 in OZR and confirmed by the augmented COX-2-mediated release of PGE 2 in coronary arteries from obese rats compared with the lean controls, as reported in diabetic mice (Przygodzki et al, 2015). Hence, COX-2 derived PGE 2 acting on vasorelaxant EP 4 receptors might have a protective role against oxidative damage induced by ROS in coronary arteries under conditions of obesity-associated insulin resistance, consistent with the protective role recently ascribed to the EP 4 receptor in obesity-related inflammation (Yasui et al, 2015) and with reports showing that VSM-specific EP 4 receptor deletion exacerbates oxidative and renal injury induced by angiotensin II in mice (Thibodeau et al, 2016). Secondly, inducible COX-2 was found in both endothelium and VSM of coronary arteries from obese rats, and further studies are needed to ascertain the source of PGE 2 in the coronary vascular wall.…”
Section: Figuresupporting
confidence: 83%
See 1 more Smart Citation
“…This was further supported by the enhanced coronary vasodilator effect found for the selective EP 4 receptor agonist TCS 2519 in OZR and confirmed by the augmented COX-2-mediated release of PGE 2 in coronary arteries from obese rats compared with the lean controls, as reported in diabetic mice (Przygodzki et al, 2015). Hence, COX-2 derived PGE 2 acting on vasorelaxant EP 4 receptors might have a protective role against oxidative damage induced by ROS in coronary arteries under conditions of obesity-associated insulin resistance, consistent with the protective role recently ascribed to the EP 4 receptor in obesity-related inflammation (Yasui et al, 2015) and with reports showing that VSM-specific EP 4 receptor deletion exacerbates oxidative and renal injury induced by angiotensin II in mice (Thibodeau et al, 2016). Secondly, inducible COX-2 was found in both endothelium and VSM of coronary arteries from obese rats, and further studies are needed to ascertain the source of PGE 2 in the coronary vascular wall.…”
Section: Figuresupporting
confidence: 83%
“…On the one hand, COX-2 represents a major source of oxidative stress and cardiovascular risk in the coronary arterial wall, but on the other, this isoenzyme is involved in protective vascular effects through the increased release of endothelial vasodilator PGE 2 , consistent with recent reports showing both protective and pro-atherogenic/pro-hypertensive effects for COX-2 under conditions of hyperlipidaemia and vascular inflammation (Tang et al, 2014). The present findings further suggest that using selective drugs to target the pathway downstream of COX-2, that is at the level of the EP 4 receptor (Yasui et al, 2015), may shift the balance of cardiovascular efficacy and risk reported for non-steroidal anti-inflammatory drugs (NSAIDS) (Bhala et al, 2013).…”
Section: Figurementioning
confidence: 66%
“…PGE2/EP4 signaling could regulate the plasticity of the macrophages. Yasui et al showed that treatment with EP4 agonist enhanced M2 polarization in wild-type peritoneal macrophages, whereas EP4-deficient macrophages were less susceptible to M2 polarization [50]. Chang et al showed that the deletion of myeloid EP4 receptors led to the decreased expression of the M2 macrophage markers, arginase-1 and IL-4Rα in APC Min/+ intestinal adenoma macrophages [51].…”
Section: Macrophagesmentioning
confidence: 99%
“…Following transport into the cell, tissue-dependent PG clearance mechanisms often take place primarily via rapid β-oxidation in the cytosolic compartment into a number of active and inactive primary metabolites. Present in virtually all nucleated cells, PGs and their receptors have been in the spotlight due to their utility as targets in many instances where these regulatory processes are perturbed, such as inflammation [13,26], cancer [27,28], and obesity [29,30]. In particular, prostaglandin F 2α (PGF2α), also termed dinoprost, is a drug used to induce labor via regulation of uterine contractions.…”
Section: Introductionmentioning
confidence: 99%